Data for: GIANT Networks: Very Deep Fully-Connected Neural Networks Applied to Microwave Problems - Stenmark, Simon (Chalmers University of Technology, 2026)
This dataset contains the samples of the training, validation and test data sets for the two numerical examples of the article ''GIANT Networks: Very Deep Fully-Connected Neural Networks Applied to Microwave Problems'' (Stenmark, Rylander, McKelvey & Ludvig-Osipov, 2026). All data is created using the finite element method as described in the article and is stored in the NPZ format which can be opened with the Python library NumPy (https://numpy.org/). The complete descriptions of all variables contained in the data are found in the article.

Detta dataset innehåller träning-, validering- och testdata för de två numeriska exemplen i artikeln "GIANT Networks: Very Deep Fully-Connected Neural Networks Applied to Microwave Problems" (Stenmark, Rylander, McKelvey & Ludvig-Osipov, 2026). Datat är skapat med hjälp av finita elementmetoden enligt beskrivning i artikeln och är lagrat i formatet NPZ som kan öppnas med Pythonbiblioteket NumPy (https://numpy.org/). Alla variabler i datasetet finns beskrivna i artikeln.
Data för: GIANT Networks: Very Deep Fully-Connected Neural Networks Applied to Microwave Problems
Keywords: neural networks (information technology); neuronnät; Jacobians; Jacobimatriser; microwave circuits; microwave filters; microwave frequencies; microwave resonance; Signal Processing; Signalbehandling; Other Electrical Engineering, Electronic Engineering, Information Engineering; Annan elektroteknik och elektronik; Artificial Intelligence; Artificiell intelligens